2022
DOI: 10.17576/akad-2022-9201-02
|View full text |Cite
|
Sign up to set email alerts
|

Pembangunan Modal Insan: Kajian Kes Program Tunas Niaga Terengganu

Abstract: Wan Mohd Zaifurin Wan naWang, nor hayati Sa'at & ibrahiM MaMat ABSTRAK Program Tunas Niaga ialah satu program pembangunan modal insan untuk memberikan kesedaran kepada pelajar sekolah menengah mengenai kepentingan keusahawanan dalam ekonomi negara. Programini bukan sahaja boleh memberi pengetahuan dan kemahiran keusahawanan kepada pelajar, malah membantu mereka membuat peralihan kerjaya selepas menamatkan program dan pengajian mereka. Justeru, kajian ini bertujuan untuk mengukur pengetahuan dan kemahiran keusa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A number of studies conducted in recent years have shown that individuals can increase their levels of entrepreneurial orientation through secondary and tertiary education [7][8][9], developing not just the knowledge base but the skills and attitudes that are necessary to be a successful entrepreneur [10]. Because of the multiplicative and accelerative effects of small enterprises on the economy, EE programs help to alleviate poverty by encouraging the formation of new firms.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conducted in recent years have shown that individuals can increase their levels of entrepreneurial orientation through secondary and tertiary education [7][8][9], developing not just the knowledge base but the skills and attitudes that are necessary to be a successful entrepreneur [10]. Because of the multiplicative and accelerative effects of small enterprises on the economy, EE programs help to alleviate poverty by encouraging the formation of new firms.…”
Section: Introductionmentioning
confidence: 99%